Analisis Tingkat Kepuasan Pelanggan terhadap Kualitas Layanan Jasa yang Diberikan oleh Meazza Futsal di Denpasar - Mohamad Edo Hari Saputra; Suratmin Suratmin; Wasti Danardani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the level of customer satisfaction with the services provided at Meazza Futsal Denpasar. Using a descriptive quantitative approach with survey methods, the research involved 100 consumers as the population, all of whom also constituted the sample through accidental sampling. Data collection was carried out using two instruments: a closed-ended questionnaire with five answer choices and an interview guide. The questionnaire was distributed to 100 respondents who were willing to participate. The data were then analyzed using a quantitative descriptive technique with percentage calculations. The results showed that customer satisfaction levels in terms of service quality at Meazza Futsal Denpasar are generally categorized as very satisfied. Specifically, the satisfaction indicators included reliability (52%), responsiveness (42%), assurance (48%), and empathy (50%), with reliability and empathy being the highest contributors to satisfaction. These findings indicate that customers perceive the services provided by Meazza Futsal as meeting or exceeding expectations across most service dimensions. The implication of this study is that the management of Meazza Futsal should continue maintaining the quality of its services while also seeking opportunities for improvement, especially in areas such as responsiveness, to ensure consistent customer satisfaction. Overall, this research reinforces the importance of regular service evaluation and customer feedback in maintaining a competitive advantage in the sports service industry. In addition, this study can serve as a valuable reference for other similar businesses aiming to enhance their service quality. Future researchers are encouraged to examine broader variables such as pricing strategy, facility maintenance, and customer engagement to obtain a more comprehensive understanding of factors influencing customer satisfaction in the sports service sector.